Human Values
VIII, 272 p.
Keywords: In recent decades, the revival of natural law theory in modern moral philosophy has been an exciting and important development. Human Values brings together an international group of moral philosophers who in various respects share the aims and ideals of natural law ethics. In their diverse ways, these authors make distinctive and original contributions to the continuing project of developing natural law ethics as a comprehensive treatment of modern ethical theory and practice.